THE EFFECT OF CARBON EMISSION DISCLOSURE, SUSTAINABILITY REPORTING, AND PROFITABILITY ON FIRM VALUE, WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE (AN EMPIRICAL STUDY OF ENERGY SECTOR COMPANIES IN INDONESIA AND MALAYSIA) - Karina Tika Sari; Kiko Armenita Julito (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study was conducted to evaluate the impact of three variables on a company's value. Furthermore, this study aims to investigate the function of effective corporate governance as a moderating element in relation to these factors. The focus of the study is on companies in the energy sector in Indonesia and Malaysia. The approach applied is a quantitative method, which is tested through path analysis. Path analysis includes testing direct effects and moderating effects. Moderating effects are performed using interaction techniques, namely the interaction between moderating variables and independent variables. The evaluation was conducted on factors that affect company value, such as carbon emission disclosure, sustainability reporting, profitability, and good corporate governance. The sample selected included 20 companies, consisting of the 10 largest energy companies in Indonesia and the 10 largest energy companies in Malaysia. Data processing was carried out with the support of Stata software. The findings of this study can serve as a basis for improving sustainability reporting and corporate governance standards, thereby promoting greater transparency and accountability. On the other hand, further research is recommended to expand the scope of the research objects and time frame, add other factors such as company size, environmental risk, or environmentally friendly innovation, and apply alternative methodological approaches to provide deeper insights into the elements that contribute to company value. The conclusion of this study shows that carbon emissions disclosure and profitability do not have a significant impact on company value. Instead, sustainability reporting has a meaningful influence. In addition, good corporate governance plays a crucial role as a moderating variable, whereby good corporate governance can strengthen the three independent variables.